2016
DOI: 10.1007/s10147-016-1054-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk scores as useful predictors of perioperative complications in patients with rectal cancer who received radical surgery

Abstract: BackgroundRectal cancer is associated with a higher rate of surgical complications. The ability to predict the risk of complications before treatment would facilitate the design of personalized treatment strategies optimally suited for each patient.MethodsWe retrospectively studied 260 patients with rectal cancer who underwent radical surgery to examine the relations between complications and 5 types of risk scores.ResultsComplications developed in 56 patients (21.5%). Nineteen patients had infectious complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…This was confirmed also in the present study considering the rate of postoperative concomitant complications, length of stay, and 30-day mortality, which were significantly higher in patients with AL than in those with an uncomplicated postoperative course. The rate of AL in our series (7.4%) was similar to that reported in other recent articles [10,15]. AL patients in our study had lower mean BMI values in comparison to those without AL, and BMI was found to be an independent factor influencing AL in multivariate analysis; this result is somewhat unexpected, considering that obesity is traditionally considered one of the main risk factors of AL [21].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This was confirmed also in the present study considering the rate of postoperative concomitant complications, length of stay, and 30-day mortality, which were significantly higher in patients with AL than in those with an uncomplicated postoperative course. The rate of AL in our series (7.4%) was similar to that reported in other recent articles [10,15]. AL patients in our study had lower mean BMI values in comparison to those without AL, and BMI was found to be an independent factor influencing AL in multivariate analysis; this result is somewhat unexpected, considering that obesity is traditionally considered one of the main risk factors of AL [21].…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the first study to evaluate the role of the dNLR, LMR, and PLR in predicting AL. These simple blood count indexes, together with the NLR and RDW, have been demonstrated to have a prognostic potential in several chronic pathological conditions, including colorectal cancer and colorectal liver metastases [22][23][24][25][26], and a potential role in predicting outcomes in surgical procedures [15][16][17][18][19][27][28][29]. NLR is the most studied index to this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations